A Mathematical Approach in Ship Navigation: The Integration of Trigonometry and Spherical Triangles in STEM Contexts - Sriantini, Ari; Abadi, Abadi (Jurnal Pendidikan MIPA, 2024)
Trigonometry and spherical triangles are branches of mathematics that are very relevant to ship navigation. Application of the concept and formula of trigonometry and spherical triangles to the positioning of ships by observing celestial bodies. Determining the true position of the ship in the sea is very important to be done so that the ship is always on the right course and avoids navigation hazards. This research aims to explore the important role of trigonometry and spherical triangles in ship navigation, as well as how learning approaches in STEM contexts can improve students' understanding and skills in determining the position of ships at sea. This research is qualitative and uses a case study approach. This study involves a real-case analysis of the application of trigonometry and spherical triangles in ship navigation to see their impact on the accuracy of ship positioning. The data collection techniques used in this research are interviews, observations, and documentation. The instruments used were validated by mathematics lecturers and astronomy navigation science lecturers. The results of the study show that trigonometry and spherical triangles have an important role in determining the position of ships at sea; STEM learning with a PBL approach has proven to be effective in improving students' understanding and skills in the application of trigonometry and spherical triangles in ship navigation. STEM learning in the context of trigonometry and spherical triangles contributes significantly to students' understanding of ship navigation and develops students' critical thinking skills.         Keywords: STEM, trigonometry, spherical triangle, problem base learning, ship navigation. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp1012-1021